Perkembangan anak - Elizabeth B. Hurlock (Erlangga)
tr, jil.1=c.1-5/tr, jil.1=c.6-13; jil.2=c.1-3/ast jil.1 =c.14/ast jil.2 =c.4/why, jil. 1=c16, jld.2=c.5/stoc1, jil.1,c.1-3,5-16 ; jil.2,c.1-5/oen, jil.2, c.6